Illegal activities and law enforcement in the Central Luangwa Valley, Zambia, from 1979 to 1992 - R. Bell; Hugo Jachmann; D. Chimbali; E. Mulonda (Pachyderm)
Reviews the effectiveness of law enforcement against poaching in the Luangwa Valley during two periods when funds were available. There was a decline, but not a halt in elephant and rhino populations in 1979-1982 when up to 22 effective wildlife scouts were engaged under the Save the Rhino Trust (SRT) funds providing an operating budget of US$15 per sq km. The illegal offtake of elephant was reduced to about 10% during the 1988-1992 period when NORAD funded the LIRDP programme which provided US$65 per sq km which led to an increase to 285 scouts in 1991. Analysis suggests that most wildlife management purposes including the conservation of elephants can be achieved for US$70 per sq km.